Primary healthcare physicians’ readiness in addressing child stunting: a review of knowledge, attitudes, and practices in Aceh Province - Tita Menawati Liansyah; Abiarso Widoseno; Iflan Naufal; Zahratulaini Zahratulaini; Ika Waraztuty; Tilaili Ibrahim; Vera Dewi Mulia; Winda Yulia; Visa Yunanda; Derevie Hendryan Moulina; Fitra Fitra; Ari Bandana Tasrif; Ariza Farizca (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Stunting remains a significant chronic nutritional problem in Indonesia, including the province of Aceh. The lack of data on the knowledge, attitudes, and practices (KAP) of primary healthcare physicians regarding stunting prevention represents a critical gap that warrants investigation. This study aimed to evaluate the levels of knowledge, attitudes, and practices of public health center (PHC) physicians in addressing childhood stunting in Aceh Province. A descriptive-quantitative design was employed involving 143 physicians from 39 PHC located in Banda Aceh and Aceh Besar. This study was conducted between April 2022 and January 2023. Data were collected using a validated and reliable questionnaire and analyzed using univariate statistics. The majority of the respondents were female (89.5%). A total of 67.8% of respondents demonstrated good knowledge, 86% exhibited positive attitudes, and 82% reported engaging in stunting prevention practices aligned with standard guidelines. In conclusion, PHC physicians in the study area displayed strong readiness to support stunting prevention efforts. Continued capacity-building interventions and sustainable support systems are essential for reinforcing their strategic role in primary healthcare services.